Clinical outcomes of peripartum cardiomyopathy: a 15-year nationwide population-based study in Asia. Issue 43 (October 2017) - Wu, Victor Chien-Chia; Chen, Tien-Hsing; Yeh, Jih-Kai; Wu, Michael; Lu, Cheng-Hui; Chen, Shao-Wei; Wu, Katie Pei-Hsuan; Cheng, Chun-Wen; Chang, Chih-Hsiang; Hung, Kuo-Chun; Chern, Ming-Shyan; Lin, Fen-Chiung; et al.
Abstract : Abstract: Peripartum cardiomyopathy (PPCM) is the development of heart failure during late pregnancy to months postpartum with potential fatal outcome. However, the disease is not well-studied in Asia. We aimed to investigate the epidemiology and clinical outcomes of PPCM in Taiwan. Electronic medical records were retrieved from Taiwan National Health Insurance Research Database from 1997 to 2011. Patients with PPCM were separated into 3 groups based on the timing of diagnosis. Early: PPCM diagnosed first to ninth month of pregnancy. Traditional: PPCM diagnosed last month of pregnancy till fifth month post-delivery. Late: PPCM diagnosed sixth to twelfth month post-delivery. Primary outcomes defined as cardiac death, all-cause mortality, and major adverse cardiovascular events (MACE) within 1 year. A total of 3, 506, 081 deliveries during 1997 to 2011 were retrieved and 925 patients with PPCM were identified. Overall incidence of PPCM was 1:3, 790 during the 15 years. Early, Traditional, and Late group each had 88, 742, and 95 patients. Cardiac death occurred in 31 patients, all-cause mortality in 72 patients, and MACE in 65 patients. Late group had 2- to 3-fold event rates in cardiac death, all-cause mortality, and MACE compared with Early and Traditional groups. Cumulative incidence showed significant differences for cardiac death ( P  = .0011), all-cause mortality ( P  = .0031), and MACE ( P  = .0014) among 3 groups. Multivariate Cox model showed Late group had significantly worse outcomes after adjusted for clinical variables compared with 2 other groups. Our study is the largest national cohort among Asian countries that showed timing of diagnosis of PPCM had different outcomes. Late diagnosis portended significantly increased morbidity and mortality, even after adjusted for clinical variables. Abstract : Supplemental Digital Content is available in the text